Go : a Kidd's guide to graphic design - Kidd, Chip (Workman Publishing, 2013)
Kids love to express themselves, and are designers by nature - whether making posters for school, deciding what to hang in their rooms, or creating personalized notebook covers. Go, by the award-winning graphic designer Chip Kidd, is a stunning introduction to the ways in which a designer communicates his or her ideas to the world. It's written and designed just for those curious kids, not to mention their savvy parents, who want to learn the secret of how to make things dynamic and interesting.